Foundation for personal and business excellence - Anand, Kailash N.; Chowdhary, Rai (Haryana: Wisdom Village Publication Pvt. Ltd, 2012)
esearch shows that if you work 8 hours a day only 1 hour of work has been of value 7 hours have been wasted. This means there is a huge opportunity to improve. A simple and effective way to get started is by implementing 5-S. It is simple yet powerful and can be practiced by everyone regardless of occupation and position. About the Author US based quality expert, Rai Chowdhary with over 25 years of experience with organizations such as NASA, Abbott Labs, Frito-Lay, Larsen and Toubro, is an award winning speaker, entrepreneur, business coach, has authored life-changing book Do-MAgIC - 7 Steps to Winning and serves on several international Technical committees. You may reach him at rai_chowdhary@yahoo.com. A former Professor with ISI, Kailash Anand has been on a mission, spreading quality awareness and analytical techniques across India and abroad, training more than 10,000 executives, and helping turn many loss making companies in to profit making ventures,publishing several papers in international journals and authoring path breaking book High Quality at an Economical Cost. You may reach him atknaisi.
What is 5-S -- Why 5-S -- Where do you Stand in 5-S -- First S- Seiri or Short -- Second S- Seiton or store -- Third S -Seiso or Shine -- Fourth S- Seiketsu or Standardize -- Fifth S- Shitsuke or Sustain -- Road Map for Implementation -- Role of 5-S in Lean and Quality -- Major Pitfalls in 5-S Implementation -- Case Studies -- Medicine Cabinet in a Hospital -- Computer Desktop in Office -- Space Management in a Motel Chain -- 5-S For Families
Includes annexure
Keywords: Economics; Business Management